2020
DOI: 10.1111/ocr.12421
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar bone changes in maxillary and mandibular anterior teeth during orthodontic treatment: A systematic review and meta‐analysis

Abstract: The association between tooth movement and remodelling of surrounding bone is controversial. To analyse the effect of tooth movement on alveolar bone changes in maxillary and mandibular anterior teeth by cone‐beam computed tomography (CBCT). The Embase, Cochrane Library and Medline databases were searched without any language restrictions. Longitudinal studies using CBCT to observe alveolar bone changes of maxillary and mandibular anterior teeth during orthodontic treatment were included. Two independent revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
2
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 36 publications
2
28
2
5
Order By: Relevance
“…The IC is a conduit between the nasal and oral cavities and houses a neurovascular bundle consisting of the nasopalatine nerve, greater palatine and a branch of the sphenopalatine arteries. Like other hard and soft tissues containing nerves and blood vessels, it has the potential to respond to stimuli, including orthodontic tooth movement, 10 through regional remodelling changes 5,16‐19 . Interestingly, our results also demonstrate that, to some degree, the IC remodels 3‐dimensionally.…”
Section: Discussionsupporting
confidence: 57%
“…The IC is a conduit between the nasal and oral cavities and houses a neurovascular bundle consisting of the nasopalatine nerve, greater palatine and a branch of the sphenopalatine arteries. Like other hard and soft tissues containing nerves and blood vessels, it has the potential to respond to stimuli, including orthodontic tooth movement, 10 through regional remodelling changes 5,16‐19 . Interestingly, our results also demonstrate that, to some degree, the IC remodels 3‐dimensionally.…”
Section: Discussionsupporting
confidence: 57%
“…The control of retraction movement (more root than crown movement) enhanced preservation on bone height and thickness [ 30 ]. The results of this narrative review confirm the statements from systematic review by Guo et al They concluded that alveolar bone height and thickness, especially at the cervical level, decreased during both labial and lingual movement of anterior teeth [ 38 ].…”
Section: Discussionsupporting
confidence: 84%
“…However, on the basis of a meta-analysis, bone remodeling is not stable after retraction. Both alveolar bone loss on the lingual side and alveolar bone gain on the labial side were obvious 1–3 months after retraction but less obvious after orthodontic treatment [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some CBCT studies have indicated that canine roots are usually positioned close to the maxillary cortical bone [ 24 , 25 ]. In a previous systematic review, we found that maxillary canines had a high risk of alveolar bone dehiscence and fenestration in extraction patients [ 26 ]. Therefore, lingual root torque control of the canines should be enhanced in extraction cases.…”
Section: Discussionmentioning
confidence: 99%